Smart Carretilla Enterprise : “SC System” / Anisah Atirah Kamaruzzaman...[et.al] - Kamaruzzaman, Anisah Atirah; Mokhtar, Nurul Syazwani; Abdul Hisam, Mohamad Afi; Nasarudin, Farah Dania; Yahya, Nur Atiqah; Mohamad Nazri, Siti Nazirah (Faculty of Plantation and Agrotechnology, 2017)
Smart Carretilla is an enterprise that focuses on the production of smart shopping cart systems used by consumers of grocery stores. The company acts upon in the form of business partners between the managers. The General Manager who also plays an important role in the company is held by Ms. Anisah Atirah Binti Kamaruzzaman. The second most important role is the Administrative Manager whose position is held by Ms. Nurul Syazwani Binti Mokhtar. The Marketing Manager on the other hand is being held by Mr. Mohamad Afi Bin Abdul Hisam. To assist the Marketing Manager, Ms. Farah Dania Binti Nasarudin holds the position of Assistant Marketing Manager. Our Operation Manager is Ms. Nur Atiqah Binti Yahya. Last but not least , our Financial Manager is held by Ms. Siti Nazirah Binti Mohamad Nazri.